Speculative Behavior in Vacant Land Development: Evidence for Real Options in Malaysia - Razak M.Z.; Khalid H.; Mohamad A. (Blackwell Publishing Ltd, 2024)
The development of vacant land may be seen from a real options perspective' owners of vacant land have the incentive to delay developing the land and keep their options open (keep the lands undeveloped) if they believe that future development will yield higher value. We investigate whether there is speculative behavior with regard to vacant land development in Malaysia. Using samples of 254 vacant plots of lands and 3,681 houses in Selangor, Malaysia, we find that the option premium for vacant lands ranges from 8% to 20% across all areas in Selangor. We posit that the higher option premium for vacant lands is the result of a higher level of speculation by landowners. We also find that, while the option value increases, the intrinsic value reduces the market price of the vacant land. Our findings are indicative of speculative behavior by the owners of vacant land in Malaysia. 2018 Institute of Developing Economies